Management in formative research to strengthen investigative competencies in officers of the Naval War Academy - Rivadeneira-Yacelga, Marco Iván Rivadeneira-Yacelga; López-Piza, Fany Alejandra; Real-Pérez, Grether Lucía; Sánchez-Bonilla, Angélica María (International Journal of Membrane Science and Technology, 2023)
The aim of this research is to define the structure of a management model based on formative research to optimise the research skills of student officers of the Staff Course of the Naval War Academy of Ecuador. The methodological approach is quantitative, descriptive, with a non-experimental cross-sectional design. The data was collected through a Likert scale survey, its reliability was measured with Cronbach's alpha and its normality with the Shapiro-Wilk test. The behaviour of the data was analysed by frequency tabulation. The MICMAC program was used as a structural analysis tool to identify key variables and their potential impacts within a formative research management model at the Naval War Academy, based on a study of global, regional and local regulations. The research found that formative research workshops are a key strategy whose multiplier effect increases research capacity and productivity. They become spaces for multidisciplinary groups that benefit from shared experiences and help to generate differential skills and capabilities, enabling students to compete in the labour market after fulfilling their academic goals.